2014
DOI: 10.3758/s13423-014-0740-0
|View full text |Cite
|
Sign up to set email alerts
|

Do not count too slowly: evidence for a temporal limitation in short-term memory

Abstract: Some data in the time perception literature have indicated that Weber's law for time does not hold: The Weber fraction gets higher with longer intervals. It is posited that this increase may reflect a fundamental information-processing limitation. If that is true, counting at a pace at which the intervals between counts remain within this capacity limitation should be more accurate than counting with intervals exceeding this capacity. In a task in which participants had to count up to a target number for a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
(28 reference statements)
1
13
0
1
Order By: Relevance
“…All of the remaining interactions exhibited F values below 1.5, p > 0.25. The data suggest that the difference between 1024 and 1431 ms violate the scalar principle, consistent with previous studies (Madison 2001(Madison , 2004b(Madison , 2006Grondin et al 2015). We tested this specifically for CV Local by comparing adjacent levels of ISI for each group and pre-post session separately, which amounts to 12 contrasts in total.…”
Section: Cognitive Taskssupporting
confidence: 74%
“…All of the remaining interactions exhibited F values below 1.5, p > 0.25. The data suggest that the difference between 1024 and 1431 ms violate the scalar principle, consistent with previous studies (Madison 2001(Madison , 2004b(Madison , 2006Grondin et al 2015). We tested this specifically for CV Local by comparing adjacent levels of ISI for each group and pre-post session separately, which amounts to 12 contrasts in total.…”
Section: Cognitive Taskssupporting
confidence: 74%
“…As can be observed in the graphs, the effect of this basal variability reduces at longer elapsed times. However, a recent study in which Grondin and colleagues asked subjects to count at different speeds showed that Weber fraction increased in proportion to the interval length used to subdivide a large total time and that this effect persisted for elapsed times of up to 24 s (Grondin et al, 2015). Their results also showed that mean produced time was always shorter than real elapsed time.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have revealed several spans that they think might involve different processes: 100 ms (Block 1979) to about 1.3 s (Grondin 2010;Grondin, Laflamme, & Mioni, 2015), 3 s (Pöppel 1978), or 7 s (James 1890), and of course even longer. We distinguish between these.…”
mentioning
confidence: 99%